ANALISIS KADAR TANIN DAUN GAYAM (Inocarpus fagifer Fosb.) PADA KETINGGIAN TEMPAT YANG BERBEDA - Lekahena, Viona Putri; Smith, Alwi; Muskitta, Marike (Program Studi Pendidikan Biologi FKIP Unpatti, 2024)
Background: Gayam (Inocarpus fagifer Fosb.) contains natural chemicals in the form of primary metabolites which play an important role in the survival of the style plant, not only primary metabolites, but the style plant contains secondary metabolites which are beneficial for the survival of the style plant in its environment Methods: The aim of this research was to determine the tannin content of gayam leaves at different altitudes. The method used in this research is descriptive quantitative and qualitative with a sampling technique using purposive sampling. Results: The results of the research show that based on photochemical tests, gayam leaves in Negeri Ema and Airlouw Hamlet contain tannin compounds. The total tannin content in Negeri Ema was 1.3956 mgTAE/g, while Airlouw Hamlet was 1.5484 mgTAE/g, which means the tannin content was higher in Airlouw Hamlet. The implication of the research results for biology learning is by creating a practical guide for biochemistry courses Conclusion: the tannin content of Gayam (Inocarpus fagifer Fosb.) leaves in Negeri Ema (highlands) is 1.3956 mgTAE/g, while the tannin content of Gayam (Inocarpus fagifer Fosb.) leaves in Air Louw Hamlet (lowlands) is 1.5484 mgTAE/g. So the tannin content in the lowlands is greater than the tannin content in the highlands